Decent work and a good life: postpandemic risks of deprivation for the dominated classes - Altreiter, Carina (Momentum Quarterly, 2023)
The paper argues that the pandemic-related health and economic crisis exacerbates existing social inequalities resulting in a considerable deprivation of the dominated classes to realize claims to a good life in general and decent work more in particular. Based on the re-analysis of current available research data on the Covid-19 pandemic in Austria, implications for social integration, recognition, as well as work-life-balance are discussed. The paper shows that the dominated classes have been affected disproportionately by the adverse health and economic effects of the crisis which exacerbate already long-standing dynamics of increased vulnerability. However, the multiple experiences of deprivation amongst the dominated class can no longer be adequately addressed in a society characterized by ‘class oblivion’.
Keywords: social class; covid-19 pandemic; decent work; recognition - working conditions